2020
DOI: 10.32794/mr11250069
|View full text |Cite
|
Sign up to set email alerts
|

The potential of melatonin in the prevention and attenuation of oxidative hemolysis and myocardial injury from cd147 SARS-CoV-2 spike protein receptor binding

Abstract: The rapid escalation of pandemic health threats associated with the novel, pathogenic SARS-CoV-2 coronavirus poses unprecedented challenges as proven effective vaccines and drugs have yet to be produced. Refractory hypoxemia and myocardial injury have been observed as two of the major causes of fatality in COVID-19 patients. SARS-CoV-2 spike (S) protein binding to broadly expressed CD147 receptors on erythrocytes causes oxidative hemolysis that may result in refractory hypoxemia and myocardial injury. Both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 239 publications
(291 reference statements)
0
41
0
Order By: Relevance
“…Melatonin is significantly involved in the complex network of psycho-neuroendocrine immunology (PNEI), stress management and aging mechanisms [ 103 ]; furthermore, this compound interacts with cortisol and with a series of immunity and inflammasome pathways, which have been shown to derange in COVID-19 [ 104 ]. This molecule has been repeatedly considered a potentially useful compound in COVID-19 patients [ 48 , 105 , 106 , 107 ]. In fact, in these cases, it may reduce the documented extremely high mitochondria oxidative stress, namely, in lung cells [ 108 ], while conferring a general antioxidant action [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin is significantly involved in the complex network of psycho-neuroendocrine immunology (PNEI), stress management and aging mechanisms [ 103 ]; furthermore, this compound interacts with cortisol and with a series of immunity and inflammasome pathways, which have been shown to derange in COVID-19 [ 104 ]. This molecule has been repeatedly considered a potentially useful compound in COVID-19 patients [ 48 , 105 , 106 , 107 ]. In fact, in these cases, it may reduce the documented extremely high mitochondria oxidative stress, namely, in lung cells [ 108 ], while conferring a general antioxidant action [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, melatonin is known to interact with CD147, a favorite Sars-Cov-2 cell receptor which is diffused in cell walls, erythrocyte and endothelium specifically. This specific feature has been regarded as a protective mechanism against a few pathologic pathways which may occur during COVID-19, such as hemoglobin denaturation, iron accumulation, hypoxia, cardiomyocytes injury and hypercoagulability [ 104 , 106 , 113 ]. Very preliminary clinical data correlate the better survival rate of COVID-19 intubated patients with melatonin exposure [ 114 ]; similarly, a small randomized clinical trial has shown a statistically significant improvement in clinical and instrumental findings in a group of patients treated additionally with melatonin, with a more rapid hospital discharge and return to baseline health [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major activities of melatonin are not directed towards the virus per se and, thus, it does not kill the virus, but rather buffers the immune response of the host and increases the tolerance of the host to the virus infection [ 26 ]. Additional assumptions that melatonin may help to block virus entry into cells have also been hypothesized [ 28 , 42 ]. Regardless of this possibility, melatonin seems to reduce the severity and mortality for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease-19 (COVID- 19) was regarded as an infective-inflammatory viral disease, which mainly affected lungs. SARS-CoV-2 virus attacked cells containing angiotensin-converting enzyme2 (ACE2), particularly surfactantproducing alveolar type II cells.…”
Section: Before the Onset Of Viral Attackmentioning
confidence: 99%